THE CULTURE CODE: HOW HR SHAPES AND SUSTAINS ORGANIZATIONAL VALUES - Ria Muazizah; Tibrani; Lukmanul Hakim (RADJA PUBLIKA, 2026)
This paper investigates the strategic role of integrated Human Resources (HR) systems in translating organizational values into measurable business performance and employee experience outcomes. Employing a comparative analysis of transactional versus value-centric HR frameworks across key functions—onboarding, performance management, and overall employee experience, this study aims to quantify the impact of coherent cultural reinforcement. The results demonstrate that organizations employing ritualized, immersive onboarding achieve a 50% greater increase in productivity and foster cultural connection 18 months faster. Furthermore, performance systems that explicitly reward value-based behaviors significantly bridge the